Blue Light Improves Vase Life of Carnation Cut Flowers Through Its Effect on the Antioxidant Defense System - Aalifar, Mostafa; Aliniaeifard, Sasan; Arab, Mostafa; Zare Mehrjerdi, Mahboobeh; Dianati Daylami, Shirin; Serek, Margrethe; Woltering, Ernst; Li, Tao (Frontiers in Plant Science, 2020)
Improving marketability and extension of vase life of cut flowers has practical significance for the development of the cut flower industry. Although considerable efforts have been made over many years to improve the vase life of cut flowers through controlling the immediate environment and through post-harvest use of floral preservatives, the impact of lighting environment on vase life has been largely overlooked. In the current study, the effect of three LED light spectra [white (400–730 nm), blue (peak at 460 nm), and red (peak at 660 nm)] at 150 μmol m–2 s–1 on vase life and on physiological and biochemical characteristics of carnation cut flowers was investigated. Exposure to blue light (BL) considerably delayed senescence and improved vase life over that of flowers exposed to red light (RL) and white light (WL). H2O2 and malondialdehyde (MDA) contents in petals gradually increased during vase life; the increase was lowest in BL-exposed flowers. As a consequence, BL-exposed flowers maintained a higher membrane stability index (MSI) compared to RL- and WL-exposed flowers. A higher activity of antioxidant enzymes [superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX)] was detected in petals of BL-exposed flowers, compared to their activities in RL- and WL-exposed flowers. In BL-exposed flowers, the decline in petal carotenoid contents was delayed in comparison to RL- and WL-exposed flowers. Maximum quantum efficiency of photosystem II (Fv/Fm) and a higher percentage of open stomata were observed in leaves of BL-exposed flowers. Sucrose and glucose contents accumulated in petals during vase life; sugar concentrations were higher in BL-exposed flowers than in RL- and WL-exposed flowers. It is concluded that BL exposure improves the vase life of carnation cut flowers through its effect on the antioxidant defense system in petals and on photosynthetic performance in the leaves.